Technogenic landforms: conceptual framework and application to geomorphologic mapping of artificial ground and landscapes as transformed by human geological action. - Peloggia, Alex Ubiratan Goossens; Silva, Érika Cristina Nesta; Nunes, João Osvaldo Rodrigues (Quaternary and Environmental Geosciences, 2014)
ABSTRACT The shaping of the Earth’s surface by Man’s geological action has produced original landform types, namely technogenic landforms. In this paper we will revise the conceptual framework concerning the geomorphic agency of mankind and introduce a new proposal for classifying these new landforms, which join the existing criteria for the identification of technogenic processes, the analysis of technogenic layers and the characterisation of the resulting newly formed technogenic ground. The proposal itself is enhanced by a taxonomic classification which considers the technogenic landforms as constituent parts of the land shape compartments that, by their way, form extensive technogenic landscapes. The classification was applied to the geomorphologic mapping of two urban areas in Presidente Prudente City (São Paulo State, Brazil) in which technogenic ground occurs. RESUMO A modelagem da superfície da Terra pela ação geológica do Homem tem produzido tipos originais de formas de relevo tecnogênicas. Neste trabalho é revisado o quadro conceitual concernente à ação geomorfológica da humanidade e introduzida uma proposta de classificação dessas novas formas de relevo, segundo os critérios de identificação dos processos tecnogênicos, as análises das camadas tecnogênicas e a caracterização do resultante terreno tecnogênico recém-formado. A proposta referida e desenvolvida por uma abordagem taxonômica que considera as formas de relevo tecnogênicas como partes integrantes de compartimentos de modelado tecnogênico que, por seu lado, formam paisagens tecnogênicas mais amplas. A classificação foi aplicada ao mapeamento geomorfológico de duas áreas urbanas na cidade de Presidente Prudente (Estado de São Paulo, Brasil) onde ocorrem terrenos tecnogênicos.